2020
DOI: 10.1093/ofid/ofaa481
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir Use in Patients Requiring Mechanical Ventilation due to COVID-19

Abstract: Background Remdesivir has been associated with accelerated recovery of severe COVID-19. However, whether it is beneficial also in patients requiring mechanical ventilation is uncertain. Methods All consecutive ICU patients requiring mechanical ventilation due to COVID-19 were enrolled. Univariate and multivariable Cox models were used to explore the possible association between in-hospital death or hospital discharge, conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
2
21
1
3
Order By: Relevance
“…In this retrospective analysis of data from an active surveillance programme, we assessed e cacy and safety of remdesivir by measuring the clinical outcomes (cure, improvement, no improvement, or death) in hospitalised patients with COVID-19 who were treated with remdesivir, and their subgroups. The cure/improvement rate was 84%, which is in accordance with the cure/improvement reported in historical cohorts [8][9][10][11][12][13][14][15]. Most patients were male, were in the age group of 40-60 years, required oxygen therapy, and received remdesivir for 5 days.…”
Section: Discussionsupporting
confidence: 86%
“…In this retrospective analysis of data from an active surveillance programme, we assessed e cacy and safety of remdesivir by measuring the clinical outcomes (cure, improvement, no improvement, or death) in hospitalised patients with COVID-19 who were treated with remdesivir, and their subgroups. The cure/improvement rate was 84%, which is in accordance with the cure/improvement reported in historical cohorts [8][9][10][11][12][13][14][15]. Most patients were male, were in the age group of 40-60 years, required oxygen therapy, and received remdesivir for 5 days.…”
Section: Discussionsupporting
confidence: 86%
“…In the latter study, however, the trial has not been designed to primarily test the time to recovery [ 39 ]. Moreover, other observational studies have shown the benefits of Remdesivir even for ventilated patients [ 40 , 41 ]. Next, hospital costs where assumed to be related at some extend to the patients length of stay.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…As a result, the competing risk analysis showed that remdesivir was significantly associated with hospital discharge (hazard ratio, 2.25; 95%CI 1.27-3.97) and with a non-significantly lower mortality (hazard ratio, 0.73; 95%CI 0.26-2.1). Moreover, the cumulative hazard plots were used to visualize potential treatment effects [44]. This example addresses all three methodological biases and clearly demonstrates the need to study competing events.…”
Section: Discussionmentioning
confidence: 99%